DIFFERENT GLOBAL CONTEXTS OF THE CONFUCIUS INSTITUTE: A SYSTEMATIC REVIEW OF THE LITERATURE - Nascimento, Ademir Macedo; Xu, Kerou (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2024)
The debate on the Confucius Institute provides a comprehensive view of observation that enriches the understanding of China on the international stage, as well as the stance and participation of other countries in the face of China's integration into the world. In order to analyze the current state of this subject, systematic review methods and procedures were adopted. 25 articles that contemplate the Confucius Institute's praxis in the main continents and countries: Africa, Asia and the USA, as well as comparisons with European language and culture institutions, were included in the reference of this study. As a result, it was possible to identify and summarize some trends; such as research scopes, recurring themes, theories and methodologies used, regional characteristics, successes and controversies.